Emergency management system in Indonesia: An evaluation of emergency patient management in 2020 - Cahyono, Agung; Lestari, Fatma; Prasetyo, Sabarinah; Tejamaya, Mila (Asia Pacific journal of health management, 2022)
Indonesia has its emergency patient management system regulated in Public Safety Center (PSC) 119 as stated in Indonesia's Health Ministry Regulation No. 19 (2016). An evaluation to assess the ongoing management of this system is a must to ensure its continuous development. This study assessed the ongoing emergency patient management system using instrument indicator questionnaires developed by the authors. The questionnaire consists of 28 indicators from 8 assessment aspects including: policy, planning, program implementation, communication, transportation, referral, management reviews, and emergency services. Questionnaires were distributed and completed questionnaires were received from 88 respondents from 21 provinces of Indonesia. Validity test results counted the coefficient correlation of all indicators above r value table (0.2096) and all Alpha Cronbach's indicators value above 0,80. The value indicator is considered poor if its average score is below the average score of the overall indicators and is considered good if it is above the average overall indicator score. The assessment result there is twelve indicators from this study shows a below average value (66). Data acquired in this study can be used as a preliminary reference for continuous improvement of Indonesia's emergency management system operated by the PSC.